Plasmonic library based on substrate-supported gradiential plasmonic arrays - Mueller, Mareen B.; Kuttner, Christian; Koenig, Tobias A. F.; Tsukruk, Vladimir V.; Foerster, Stephan; Karg, Matthias; Fery, Andreas (ACS nano, 2014)
We present a versatile approach to produce macroscopic, substrate-supported arrays of plasmonic nanoparticles with well-defined interparticle spacing and a continuous particle size gradient. The arrays thus present a "plasmonic library" of locally noncoupling plasmonic particles of different sizes, which can serve as a platform for future combinatorial screening of size effects. The structures were prepared by substrate assembly of gold-core/poly(N-isopropylacrylamide)-shell particles and subsequent post-modification. Coupling of the localized surface plasmon resonance (LSPR) could be avoided since the polymer shell separates the encapsulated gold cores. To produce a particle array with a broad range of well-defined but laterally distinguishable particle sizes, the substrate was dip-coated in a growth solution, which resulted in an overgrowth of the gold cores controlled by the local exposure time. The kinetics was quantitatively analyzed and found to be diffusion rate controlled, allowing for precise tuning of particle size by adjusting the withdrawal speed. We determined the kinetics of the overgrowth process, investigated the LSPRs along the gradient by UV-vis extinction spectroscopy, and compared the spectroscopic results to the predictions from Mie theory, indicating the absence of local interparticle coupling. We finally discuss potential applications of these substrate-supported plasmonic particle libraries and perspectives toward extending the concept from size to composition variation and screening of plasmonic coupling effects.
CRIS-Team Scopus Importer:2023-03-20
Keywords: core/shell particles; gradient assemblies; localized surface plasmon resonance; plasmonic library; PNIPAM; screening substrate; surface modification